2024
DOI: 10.1371/journal.pone.0296669
|View full text |Cite
|
Sign up to set email alerts
|

Reported side-effects following Oxford/AstraZeneca COVID-19 vaccine in the north-west province, Iran: A cross-sectional study

Majid Eterafi,
Nasrin Fouladi,
Majid Golizadeh
et al.

Abstract: While the vaccination was introduced as a promising tool to control the Coronavirus disease 2019 (COVID-19) pandemic, concerns about vaccine-related side effects had grown. Due to the widespread administration of the COVID-19 vaccine worldwide for the first time, it was necessary to evaluate the safety and potential side effects in recipients. This study aims to assess, the incidence of adverse effects following Oxford-AstraZeneca vaccination and identify their related factors. In this cross-sectional survey-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…In this study, thrombosis events are predominantly associated with the AZ vaccine, consistent with previous research [8,9]. AEFI complaints were more common after the first dose of the AZ vaccine, aligning with existing literature [10]. Despite reports of higher AEFI rates after the second dose of mRNA vaccines [2], our study found more AEFI after the first dose of mRNA vaccines.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, thrombosis events are predominantly associated with the AZ vaccine, consistent with previous research [8,9]. AEFI complaints were more common after the first dose of the AZ vaccine, aligning with existing literature [10]. Despite reports of higher AEFI rates after the second dose of mRNA vaccines [2], our study found more AEFI after the first dose of mRNA vaccines.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, thrombosis events were predominantly associated with the AZ vaccine, consistent with previous research [8,9]. AEFI complaints were more common after the first dose of the AZ vaccine, aligning with the existing literature [10]. Despite reports of higher AEFI rates after the second dose of mRNA vaccines [2], our study found more AEFI after the first dose of mRNA vaccines.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to conventional technologies, the COVID-19 pandemic catalyzed advancements in novel vaccine platforms [6]. The BNT162 mRNA vaccine, developed by Pfizer-BioNTech, and the ChAdOx1 adenoviral vector vaccine, developed by the University of Oxford-AstraZeneca, were the initial vaccines endorsed by the World Health Organization (WHO) for emergency deployment [7]. They have predominantly been adopted worldwide, complemented by the administration of other vaccines, such as the inactivated virus vaccine CoronaVac (Sinovac), which has primarily been distributed in low-and middle-income nations [8,9]; together, they markedly reduced the infection rates, severity, and mortality, preventing millions of deaths [10].…”
Section: Introductionmentioning
confidence: 99%